THE RIGHT OF PEDAGOGICAL VETO: DEVELOPING CRITICAL REFLECTION SKILLS IN FUTURE TEACHERS WHEN WORKING WITH GENERATIVE ARTIFICIAL INTELLIGENCE ’HALLUCINATIONS’ (Uzbekistan Open Conference, 2026)
The rapid integration of large language models (LLM) into pedagogical practice highlights the problem of critical assessment of machine-generated content by future teachers. This article presents the results of a quasi-experimental study aimed at developing a reflective-personal mechanism in educators working with generative AI tools. Based on the author’s platform ’Lesson and Task Generator’, the effectiveness of the peer-review methodology and professional reflective journals (RJS-2024) has been proven. The study demonstrates that controlled exposure of future teachers to AI ’hallucinations’ is a powerful catalyst for developing their professional expertise and responsibility.